1993
DOI: 10.1111/j.1460-9568.1993.tb00971.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Enfolding of Olfactory Neurites by p75 NGF Receptor Positive Ensheathing Cells from Adult Rat Olfactory Bulb

Abstract: Secondary cultures of adult rat olfactory bulb (OB) contained three different types of cell: (i) process-bearing cells; (ii) macrophage-like cells and (iii) fusiform cells. The immunohistochemical properties of process-bearing cells closely corresponded to those described for ensheathing glia in vivo. The most distinctive feature of these cells was their immunoreactivity for low affinity nerve growth factor receptor (NGFR). Process-bearing cells also shared the ultrastructural properties of ensheathing glia in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 49 publications
(61 reference statements)
1
86
0
3
Order By: Relevance
“…First, in vitro OECs express nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), glia cell line-derived neurotrophic factor (GDNF), and their receptors (Woodhall (Boruch et al, 2001) and p-75 low-affinity NGF receptor (Ramón-Cueto et al, 1993). It is well known that all these neurotrophic factors promote sprouting and regeneration of central axons.…”
Section: Discussionmentioning
confidence: 99%
“…First, in vitro OECs express nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), glia cell line-derived neurotrophic factor (GDNF), and their receptors (Woodhall (Boruch et al, 2001) and p-75 low-affinity NGF receptor (Ramón-Cueto et al, 1993). It is well known that all these neurotrophic factors promote sprouting and regeneration of central axons.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the OECs transplantation in clinic is a mixture of olfactory bulb cells, even though, the purity of OEC cultures, generated by a number of different procedures, is most often defined by the percentage of cells that express the P75NTR (Ramon-Cueto et al, 1993). This phenotypic marker is, however, common to both OECs and Schwann cells in vitro (Kawaja et al, 2009).…”
mentioning
confidence: 99%
“…One subpopulation is known as the Schwann cell-like OECs, which have a long fusiform bipolar morphology; the other is known as the astrocytelike OECs, which have a flat sheet-like morphology. Interestingly, several studies have shown that Schwann cell-like OECs are more effective in promoting axonal regeneration than astrocyte-like OECs in vitro and in vivo [11,[28][29][30]. Transplanted OECs from the lamina propria and olfactory bulb, which display differential integration and migration, promote differential axonal sprouting in the lesioned spinal cord [31].…”
Section: Introductionmentioning
confidence: 99%